Case report: Dueling etiologies: Longitudinally extensive spinal cord lesion mimicking spinal cord infarct with simultaneous positive Lyme serology and amphiphysin antibody - Kalaszi, Marianna; Donlon, Eoghan; Ahmad, Marzuki Wan; Mohamed, Abdirahman Sheikh; Boers, Peter (Frontiers in Neurology, 2022)
Background Longitudinally extensive spinal cord lesions are challenging diagnostic entities as they are uncommon, but various etiologies can cause them. Case report We report a case of a 55-year-old man with a past medical history of hypertension. He is an ex-smoker. He presented with chest pain, followed by right lower limb weakness, preceded by 2 weeks of constipation and voiding dysfunction. The examination revealed right lower limb mild flaccid paresis, absent reflexes, reduced anal tone, and urinary retention. His symptoms deteriorated over 24 h, and he developed severe flaccid paraparesis with impaired pinprick sensation below the T4 level. MRI spine showed an abnormal, non-enhancing signal in the anterior aspect of the spinal cord extending from the T4 level to the conus without associated edema. He was commenced on intravenous steroids and had significant improvement after one dose. The imaging was felt to be consistent with spinal cord infarction, and aspirin was started. The cerebrospinal fluid analysis showed elevated protein (0.8 mg/ml). Investigations for stroke and autoimmune pathologies were negative. The Lyme immunoblot confirmed intrathecal production of IgG to Borrelia antigens. The patient was started on ceftriaxone. The paraneoplastic screen identified amphiphysin antibodies. CT-TAP and PET-CT did not identify occult malignancy. The patient had a significant improvement over 2 months, strength was almost fully recovered, and autonomic functions returned to normal. Conclusion We describe an unusual steroid-responsive, longitudinally extensive spinal cord lesion with radiological features of spinal cord infarct and a simultaneous finding of intrathecal Lyme antibodies and serum amphiphysin antibodies.